Notes on Yurok Derivation - Proulx, Paul (Kansas Working Papers in Linguistics, 1985)
Yurok verb stems consist of one ortwo roots, often a medial suffix, and usually one or more final suffixes. When there are two roots the second is deverbal. Some roots are followed by postradical extensions. A medial suffix may follow either type of root. Different finals distinguish transitive from intransitive verbs. Some are abstract, some concrete. Elements are generally joined by one of two link vowels, e and o. Yurok nouns and particles are simpler in structure, but a few derivational finals have been identified. There are a few contractions at morpheme boundaries.